USE OF ROCK MASS RATING (RMR) VALUES FOR SUPPORT DESIGNS OF TUNNELS EXCAVATED IN SOFT ROCKS WITHOUT SQUEEZING PROBLEM - Komurlu, Eren; Demir, Serhat (GeoScience Engineering, 2019)
Effect of the rock material strength on the RMR value and tunnel support designs were investigated within this study including site works, analytical and numerical analyses. It was found that rock material strength effect is quite limited in the RMR method to determine an accurate rock mass class to design tunnel support. Since the limitation, rock mass classes are evaluated to be usually misleading and supports designed in accordance with the RMR value are insufficient for tunnels excavated in rock masses with low strength values of rock materials. Totally, five different tunnels in Turkey have been supported using a new strength adjustment factor calculated in consideration of the in-situ stress and the uniaxial compressive strength values of rock materials. As confirmed by the field applications, analytical and numerical analyses, a newly modified RMR value (RMRus) was suggested to be used in tunnel support design works. Keywords: Rock Support, Empirical Methods in Tunnelling, RMR, Rock Mass Strength, Finite Element Analyses http://doi.org/10.35180/gse-2019-0007